Immunization of mice with a peptide derived from the HTLV-1 TAX1BP1 protein induces cross-reactive antibodies against aquaporin 4. (3rd October 2015) - Kampylafka, Eleni I.; Alexopoulos, Harry; El Hamidieh, Avraam; Dalakas, Marinos C.; Andreakos, Evangelos; Tzioufas, Athanasios G.
Abstract: Antibodies against aquaporin-4 (AQP4) are specific and pathogenetic for Neuromyelitis Optica (NMO). In a previous study, three linear intracellular AQP4 B-cell epitopes were uncovered in NMO patients. A particular epitope showed high-sequence similarity with a segment of the human TAX1BP1 protein, which is necessary for the replication of HTLV-1 virus. The aim of the present study was to investigate whether immunization of mice with the TAX1BP1 peptide could produce specific antibodies against AQP4 epitopes or induce symptoms. Eight C57Bl/6 mice were immunized with TAX1BP1pep in Complete Freund's Adjuvant and eight with adjuvant only. Animals received three subcutaneous injections and sera were obtained before each immunization and at sacrifice. All sera were evaluated by ELISA for antibodies against the TAX1BP1peptide, the homologous AQP4 peptide and all linear AQP4 epitopes. Homologous and cross-inhibition assays were performed to ensure binding specificity, and reactivity against conformational AQP4 epitopes was evaluated by a cell-based assay. Sera from immunized animals showed high reactivity against the immunization peptide, and the homologous AQP4 epitope. Inhibition assays confirmed binding specificity. No antibodies were produced against any other epitopes, either linear or conformational. No clinical or brain inflammatory signs were observed in the animals. The induction of antibodies to an AQP4 epitope in mice immunized with the TAX1BP1-derived peptide suggests that a latent HTLV-1 infection could lead to TAX1BP1 antigen presentation and the production of anti-AQP4 antibodies, probably through T cell-mediated mechanisms. Further studies are needed for exploring triggering factors for NMO especially in HTLV-1-endemic regions.